David Lopez: capstone - Lopez, David, artist (Colorado State University. Libraries, 2024)
The artist's statement: As a multidisciplinary artist, David Lopez aims to explore the realms of graphic design and sculpture with a specialized eye for modern techniques and unique material approaches. His exploration and expression take inspiration from popular culture and modern music while integrating his own flair. His work combines and exhibits two distinct but harmonious mediums, where pixels and polygons intertwine with clay and forms.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design